ASSESSMENT AND CHARACTERIZATION OF COMMON SOLID WASTE FROM THE UNIVERSITY CAMPUS OF UCSM AREQUIPA PERÚ - Wilbert Felipe Zevallos Gonzales (2021)
The growing energy demand and per-capita consumption create environmental problems due to the generation of organic and inorganic waste. At present, it has been established to identify the ideal management conditions to mitigate these environmental problems and achieve sustainable development, with the implementation of waste recovery and recycling systems. In this research work, the scope of consumption and waste generation of the San José campus of the Catholic University of Santa María in Arequipa-Peru are studied, developing a waste recovery and identification system. The generation of solid waste was 0.00487 Kg / person-day, with a total daily generation of 73.78 Kg / day. The composition of common solid waste was composed of 17.28% of organic matter, being the component with the highest representativeness, the waste paper represented 12.13%, the components of plastic waste were 9.66%, cardboard 8.17%, glass 6.82% , bags 8.82%, Tetrapak 8.26%, Tecnopor 7.74%, metal 6.01%, fabrics and textiles 0.28% and finally wood and foliage 0.21%. With the results, an improvement has been established in the university’s integrated waste system, establishing primary conditions and implementing a reuse process; With the evaluation of the waste and the data obtained, a comprehensive management alternative was defined, enhancing recyclable waste, avoiding waste and raising awareness in the university community.